A chain model charactering the effect of interphase on electro-mechanical properties of particle reinforced polymer. (1st April 2020) - Chang, Mengzhou; Kong, Fangyun; Wang, Zhenqing
Abstract: In this paper, electro-mechanical properties of particle reinforced polymer composites have been investigated based on a microstructure inspired chain model. First, the chain model composed of chain, assisted chain and particle has been proposed to redefine the mechanical and electrical properties of polymers. A parameter evaluating the interphase influence has been introduced to reconstruct the structures within the model. Then, the electric response of the composites can be obtained by calculating the minimum distance along the direction of electrical path. Furthermore, the optimized responses of polymer composites have been investigated by considering several factors: interphase properties, strain and particle size. From the simulation results, it can be concluded that the model has advantage to capture the electro-mechanical behavior of composites with complex structures. Highlights: A particle-chain model is developed to solve the electro-mechanical coupling problem. Parameter evaluating the interphase influence on the chain structures is introduced. Electric properties is related to the minimum distance along electric path. Interphase properties, strain and particle have effect on electro-mechanical properties.